2016
DOI: 10.1038/srep32212
|View full text |Cite
|
Sign up to set email alerts
|

Individual dispersal decisions affect fitness via maternal rank effects in male rhesus macaques

Abstract: Natal dispersal may have considerable social, ecological and evolutionary consequences. While species-specific dispersal strategies have received much attention, individual variation in dispersal decisions and its fitness consequences remain poorly understood. We investigated causes and consequences of natal dispersal age in rhesus macaques (Macaca mulatta), a species with male dispersal. Using long-term demographic and genetic data from a semi-free ranging population on Cayo Santiago, Puerto Rico, we analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…A prominent example in NHPs is the migration from the natal group to a new group (natal dispersal). Migration is typically accompanied by increases in mortality or injury rates, decreases in access to resources, and social costs, i.e., the loss of social ties or rank (Dittus 1979;Weiß et al 2016). Following migration, male rhesus macaques show more fearful and less physically aggressive behavior than before (von Borell et al 2016), which is consistent with findings from captive pigtailed macaques, where individuals that are new to a facility are more cautious (Sussman et al 2014).…”
Section: Stressful Life Experiencessupporting
confidence: 66%
“…A prominent example in NHPs is the migration from the natal group to a new group (natal dispersal). Migration is typically accompanied by increases in mortality or injury rates, decreases in access to resources, and social costs, i.e., the loss of social ties or rank (Dittus 1979;Weiß et al 2016). Following migration, male rhesus macaques show more fearful and less physically aggressive behavior than before (von Borell et al 2016), which is consistent with findings from captive pigtailed macaques, where individuals that are new to a facility are more cautious (Sussman et al 2014).…”
Section: Stressful Life Experiencessupporting
confidence: 66%
“…The dispersal of an individual can have important consequences for individual fitness, population dynamics and spatial distributions (Clobert, Danchin, Dhondt, & Nichols, ). Movements from natal areas into habitats that provide enhanced foraging opportunities are common in many species, and this can have considerable social, ecological and evolutionary consequences (Weiß, Kulik, Ruiz‐Lambides, & Widdig, ). However, this natal dispersal can have considerable costs and tends to exist in trade‐offs with increased predation risk (Alcalay, Tsurim, & Ovadia, ; Halpin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also in the present study we did not to detect a significant relationship between EGP and male age as well as a male’s previous reproductive success in his current group of residency or his natal status. The latter is noteworthy as a previous study on factors influencing natal dispersal found that more than two-thirds of the natal males that started reproducing before dispersal were observed to engage in EGPs (Weiß et al 2016), suggesting that it might be a means for natal males to find unrelated females willing to mate with them. Similarly, EGP was more common in a population of Australian magpies, Gymnorhina tibicen , with low rates of juvenile dispersal than in a population with high dispersal rates (Durrant & Hughes, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…Research on the selective pressures that may drive males and/or females to seek EGPs has been conducted mainly in birds and, to a lesser extent, in mammals. For males, the benefits of mating outside their reproductive unit are rather straightforward as they can gain additional reproductive success through EGP (Birkhead & Møller, 1993; Fietz et al, 2000; Gibbs et al, 1990; Lawler, 2007; Trivers, 1972; Weiß, Kulik, Ruiz-Lambides, & Widdig, 2016). Benefits of EGP are less evident for females but may include both direct and indirect benefits such as the acquisition of good or compatible genes (blue tits, Parus caeruleus : Foerster, Delhey, Johnsen, Lifjeld, & Kempenaers, 2003; alpine marmots, Marmota marmota : Cohas, Yoccoz, Silva, Goossens, & Allainé, 2006; humans, Homo sapiens : Thornhill & Gangestad, 1993), avoiding costs related to inbreeding (banded mongoose, Mungos mungo : Nichols, Cant, & Sanderson, 2015), enhanced resource acquisition (Smuts, 1985; Greiling & Buss, 2000), or reduced risk of infanticide (reviewed in Wolff & MacDonald, 2004).…”
mentioning
confidence: 99%